The preparation of Ni/Mo-based ternary electrocatalysts by the self-propagating initiated nitridation reaction and their application for efficient hydrogen production. Issue 36 (11th September 2019) - Hou, Mengjie; Lan, Ruyue; Hu, Zhibiao; Chen, Zuofeng
Abstract : This work introduces a novel strategy via the in situ thermal decomposition initiated nitridation reaction for synthesizing Ni/Mo-based ternary HER electrocatalysts. Abstract : In the hydrogen evolution reaction (HER), multi-component electrocatalysts with a synergistic effect may possess enhanced catalytic activity and broadened applicability in both acidic and alkaline media. Herein, we developed a novel strategy via the self-propagating initiated nitridation reaction for the synthesis of Mo2 C, MoNi4, and Ni2 Mo3 N nanocrystals as active components assembled in a multiscale porous honeycomb-like carbon (Ni/MoCat@HCC). This strategy can be realized by simply calcining (NH4 )6 Mo7 O24 and Ni(NO3 )2 precursor hybrids under a H2 /Ar atmosphere at a fairly low temperature of 600 °C. It relies on the in situ thermal decomposition of (NH4 )6 Mo7 O24 and the subsequent nitridation reaction with released NH3, thus avoiding the continuous purging of NH3 in the conventional method. The rich reaction intermediates during the calcination of bimetallic precursors also offer other catalytically active components that are controllable by varying the calcining procedure. Benefiting from the multiscale porous structure, ultrafine size of catalyst particles, and strong synergistic effect of several catalytically active components, the as-prepared Ni/MoCat@HCC exhibits extraordinary HER electrocatalytic activity with low onset overpotentials, small Tafel slopes, and excellent cycling stability in both acidic and alkaline media, outperforming most current noble-metal-free electrocatalysts. This study paves a novel way for synthesizing multi-component electrocatalysts with enhanced catalysis performance.